Review on current seroprevalance status of common small ruminants’ bacterial and viral diseases in tropics focusing in Malaysia: a holistic of current status essential to be study and known - Jesse, Faez Firdaus Abdullah; Hashi, Hamza Abdirahman; Chung, Eric Lim Teik; Mohd Lila, Mohd Azmi (Nexus Academic Publishers, 2020)
Livestock industries are important for economic development in developing countries where small ruminant production is an important and viable sub part of animal industries in Asia. Small ruminant production systems are complex where livestock industries show a vital role in economic development and play a major role in the life of farmers in developing countries. Small ruminant industry has been facing devastating economic losses from major outbreaks of transboundary animal diseases and zoonosis potential such as Brucella, Caseous Lymphadenitis (CLA), Contagious Ecythma (orf), Caprine Arthritis Encephalitis (CAE), Coxaella burnetti (Q fever), Schmallenberg infection (SBV) and Bluetongue. These diseases have become an international nuisance as all regions around the world and particularly in tropic regions can be considered potential risk. Occurrences of these diseases will cause obstacles in the main production of the farm and livestock and need to give detail emphasis to upgrade the herd health programme and uplift disease monitoring programme to enhance biosecurity in ruminant livestock industry particularly in small ruminant. Currently Malaysian Agriculture plan is to uplift and enhance the ruminant production for food security and safety of the country. Therefore, it is important to have current seroprevalance status of common small ruminants’ bacterial and viral diseases in tropics focusing in Malaysia where a holistic of current status essential to be study and known.